2015
DOI: 10.1073/pnas.1417232112
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenesis and epicardial adipose tissue: A novel fate of the epicardium induced by mesenchymal transformation and PPARγ activation

Abstract: The hearts of many mammalian species are surrounded by an extensive layer of fat called epicardial adipose tissue (EAT). The lineage origins and determinative mechanisms of EAT development are unclear, in part because mice and other experimentally tractable model organisms are thought to not have this tissue. In this study, we show that mouse hearts have EAT, localized to a specific region in the atrial–ventricular groove. Lineage analysis indicates that this adipose tissue originates from the epicardium, a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 33 publications
6
121
0
2
Order By: Relevance
“…The outer mesothelial layer of the heart, the epicardium, contains a number of multipotent progenitor cells that can undergo an epithelial-to-mesenchymal transition (EMT) process, giving rise to multipotent mesenchymal epicardium-derived cells (EPDCs) (7)(8)(9)(10). Recently it has been shown that epicardial-derived cells differentiate into adipocytes during early postnatal development, contributing to physiological fat or EAT accumulation in the atrial-ventricular groove (10).…”
Section: Rosamentioning
confidence: 99%
“…The outer mesothelial layer of the heart, the epicardium, contains a number of multipotent progenitor cells that can undergo an epithelial-to-mesenchymal transition (EMT) process, giving rise to multipotent mesenchymal epicardium-derived cells (EPDCs) (7)(8)(9)(10). Recently it has been shown that epicardial-derived cells differentiate into adipocytes during early postnatal development, contributing to physiological fat or EAT accumulation in the atrial-ventricular groove (10).…”
Section: Rosamentioning
confidence: 99%
“…отрицательными, избыток эпикардиаль-ного жира сопровождается: гипертрофией миокарда, фиброзом и апоптозом кардиомиоциотов, снижением синтеза адипонектина и усилением образования мар-керов воспаления [46]. Равновесие между защитным и патологическим воздействием ЭЖТ крайне хрупкое.…”
Section: эпикардиальная жировая тканьunclassified
“…8 A recent study further demonstrates that the origin of human and mouse epicardial fat lies in the epicardium itself. 20 In terms of its distribution, postmortem studies have revealed that epicardial fat can cover up to 80% of the heart surface and contribute up to 20% of total ventricular weight under normal conditions, while being capable of covering the heart completely and even extending up to 2 cm in thickness during obesity in humans. 21,22 Anatomically, epicardial fat is not separated from the underlying myocardium with any fascia-like structure and is also known to share coronary blood supply with the latter, thereby supporting the idea of plausible 'vasocrine' or 'paracrine' cross talk between the two.…”
Section: Physiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%
“…Considering that rodents do not necessarily possess epicardial fat under normal conditions and even when observed (that is, due to obesity or aging), such as in the case of guinea pigs, epicardial fat distribution differs from that in humans. 20,29 Thus, species-specific differences in the biochemical, molecular as well as physiological relevance of epicardial fat can be expected, and hence it can be stated that our understanding of the human epicardial fat is quite limited at this point. By demonstrating that human and mouse epicardial adipocytes originate from ventricular epicardium that constitutively express peroxisome proliferator-associated receptor-γ in case of humans, but not in case of mice, Yamaguchi et al 20 have pinpointed such differences.…”
Section: Physiological Relevance Of Human Epicardial Fatmentioning
confidence: 99%
See 1 more Smart Citation